Professional learning communities for inclusive pedagogy: what teacher talk in professional communities reveals about teacher professional identity and agency - Kimani, Anne Wacango Muguro (University of the Witwatersrand, Johannesburg, 2023)
In-service teacher learning for inclusive pedagogy seeks to address the perceived lack of capacity for teaching in inclusive classrooms in South Africa. Research suggests that teachers feel underprepared for this task, and that the prevalent delivery models for this learning, workshops, and short courses, have done little to enable sustained inclusive practices. This study took a new direction, arguing that simply acquiring knowledge and skills for inclusive teaching misses the need to focus on teacher professional identity and agency. The professional and institutional change required for teachers to be pedagogically responsive to a range of learners, demands that professional learning address teachers’ immediate realities, be a long term, school-based professional learning programme. A three-year study in a full-service school in Johannesburg, South Africa, investigated teacher talk within professional learning communities (PLCs). PLCs are situated in practice and can promote and sustain teachers’ learning over an extended period. Wenger’s (1998) theory of learning as social practice and Sfard and Prusak’s (2005) theory of identity as narrative provided analytical insights into identity and agency in the PLCs. The subject focus of the PLCs was inclusive pedagogy, and the analysis was based on the Inclusive Pedagogical Approach in Action (IPAA) (Florian & Spratt, 2013). Using a Critical interpretivism perspective, teacher talk in the PLCs and individual teacher interviews were analysed. Analysis of teacher talk in relation to the IPAA revealed two themes of talk: Inclusive Talk and Difference Talk. “Difference Talk” showed that the enactment of inclusion cannot be rigidly defined and demarcated in advance in every situation or in every instance or be abstracted from time and place. A nuanced interpretation of difference may help researchers avoid the binary distinctions about inclusive education and inclusive pedagogy and deficit interpretations about teachers’ practices. The findings show that even though teachers talked about enacting inclusive pedagogy they did not consider themselves inclusive educators. They implied that since they had not had ‘special education training’ they could not consider themselves as inclusive educators despite saying that they had taught in an inclusive manner. Participation in the PLCs enabled teachers to negotiate meaning and create a coherent community. A coherent community allowed teachers to challenge their perspectives about teaching inclusively and to share their experiences. This study contributes a conceptual understanding of the interplay between teachers’ professional identity and the sociocultural contexts of PLCs, and how teacher talk can mediate teacher learning for inclusive pedagogy. The findings could be of interest to teacher educators in designing professional learning communities for inclusive pedagogy.
A thesis submitted in fulfilment of the requirement for the degree of Doctor of Philosophy, to the Faculty of Humanities , Wits School of Education, University of the Witwatersrand, Johannesburg, 2023
Keywords: Professional learning community; Inclusive pedagogy; Teacher professional identity; Teacher professional agency; UCTD; SDG-4: Quality education